REAL WORK RESPONSE CAPABILITY - LIU FENG; MONROY HERNANDEZ ANDRES; ZHAO YAN; JI CHUNXIN; VAISH, RAJAN; TSAI THOMAS Y (2025)
A collaborative session (e.g., a virtual time capsule) in which a user is provided with access to collaborative objects with related materials and added virtual content. In a collaboration session example, a user selects an associated material of a collaboration object. When manipulating the collaboration object, physical features are assigned to the collaboration object in accordance with the associated material perceived by the participant. In one example, a material associated with a collaborative object is a metal, where an interaction between a user and the collaborative object generates a response of the collaborative object that is indicative of physical characteristics of the metal, such as inertia, acoustics, and ductility. 一种协作会话(例如，虚拟时间胶囊)，其中，向用户提供对具有相关材料和添加的虚拟内容的协作对象的访问。在协作会话示例中，用户选择协作对象的相关联的材料。当操纵协作对象时，根据参与者感知到的相关联的材料，将物理特征分配给协作对象。在一个示例中，与协作对象相关联的材料是金属，其中，用户和协作对象之间的交互生成协作对象的响应，该响应指示金属的诸如惯性、声学和延展性的物理特性。